2009
DOI: 10.1186/1471-2091-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Redox biology of Mycobacterium tuberculosis H37Rv: protein-protein interaction between GlgB and WhiB1 involves exchange of thiol-disulfide

Abstract: Background: Mycobacterium tuberculosis, an intracellular pathogen encounters redox stress throughout its life inside the host. In order to protect itself from the redox onslaughts of host immune system, M. tuberculosis appears to have developed accessory thioredoxin-like proteins which are represented by ORFs encoding WhiB-like proteins. We have earlier reported that WhiB1/Rv3219 is a thioredoxin like protein of M. tuberculosis and functions as a protein disulfide reductase. Generally thioredoxins have many su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 39 publications
0
45
1
Order By: Relevance
“…WhiB proteins are bifunctional regulators, acting either as transcription factors or by modulating the redox state of target proteins (53)(54)(55). Whereas WhiB1, WhiB2, WhiB3, and WhiB7 have been extensively studied, little is known about WhiB4, WhiB5, and WhiB6, apart from their expression profiles and disulfide reductase activity (53,54,56,57).…”
Section: Discussionmentioning
confidence: 99%
“…WhiB proteins are bifunctional regulators, acting either as transcription factors or by modulating the redox state of target proteins (53)(54)(55). Whereas WhiB1, WhiB2, WhiB3, and WhiB7 have been extensively studied, little is known about WhiB4, WhiB5, and WhiB6, apart from their expression profiles and disulfide reductase activity (53,54,56,57).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the direct interaction between ASK1 and STRAP, a GST pull-down assay was also performed using recombinant ASK1 and STRAP proteins as described (27). Native PAGE for determining the in vitro binding between ASK1 and STRAP was performed using in vitro-translated 35 S-labeled STRAP, prepared with the TNT reticulocyte lysate system (Promega) as described previously (23) or autophosphorylated ASK1, prepared in the presence of kinase buffer (20 mM Tris-HCl, pH 7.5, 0.1 mM sodium orthovanadate, 1 mM dithiothreitol, and 20 mM MgCl 2 ) con-…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that WhiB proteins are able to bind other proteins to modify their activity through their disulfide reductase function (2,15). In order to detect possible WhiB5 interactors, we recently used a yeast two-hybrid system to analyze an M. tuberculosis expression library, using WhiB5 as bait.…”
Section: Discussionmentioning
confidence: 99%
“…WhiB1 was recently shown to be an essential protein that is able to repress its own transcription by binding to the promoter region of its structural gene (35). It was also shown to interact with GlgB [alpha(1,4)-glucan branching enzyme] and to reduce an intramolecular disulfide bond present in this protein, suggesting a role in posttranslational regulation of GlgB (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation